Social information retrieval for online community question answering services - Jun, Choi Lee; Yu-N, Cheah; Wai, Shiang Cheah (2016)
Online Community Question Answering Services is a platform that allows users to seek for answers anytime and anywhere.The services cover a large collection of unstructured knowledge and become a knowledge repository for problem solving.The answers in the services are generated by other public user.This environment creates a large collection of unstructured knowledge, which can be use as knowledge source for other intelligent processes.From the review, it is a challenge to access accurate information from the Online Community Question Answering services.This study propose a social information retrieval method to access the knowledge from the services.The proposed method query and retrieve information the online services through query expansion.Then, the retrieved information is filtered through a similarity analysis between a question with a query statement and semantic relatedness between answers and the query statement.The accuracy of the proposed approach is evaluated through human evaluation.